ANALISIS PENGARUH NPL, PROPORSI DEWAN KOMISARIS INDEPENDEN, BOPO, CAR DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Pada Bank Non Devisa di Indonesia Periode 2008-2011) - Rini, Indah Kustia; Sufian, Syuhada (Faculty of Economics and Business Diponegoro University, 2013)
Based on Indonesian Banking Statistics (SPI)Volume 10, Number 1, December 2011 showthat non foreign exchange banks grew enormously, this can be seen from the growth of Third Party Fund (DPK), Net Interest Margin (NIM) and profit for the period of the study is increasing compared to the other bank.This research used time series data from non foreign exchange bank’s annual reports for the year of 2008 until 2011. To determine sampling collection in this study, itwas conducted by usig purposive sampling method based on determined criteria. The number of valid sample is 9 banks. This research used multiple regression analysis toclassical assumption test, multiple linier regression test, and hypothesis testing which included testing, Goodness of Fit’ testing and T-test’ testing.Result of analysis show that the NPL (Non Performing Loan) and BOPO (OperationalCost Toward Return) is negative effect and significantly on the financial performance of bankingcompanies. The result study also showed that proportion of independent commissioner and CAR (Capital Adequacy Ratio)is negative effect but not significantly effect on the financial performance of banking companies, and firm size have a positive effect and significantly effect on the financial performance of banking companies